STUDI HISTORIS LABEL PADA WINE (STUDI KASUS PADA LABEL HATTEN WINES) - Made Arini Hanindharputri (Jurnal Nawala Visual, 2023)
This text discusses the concepts of packaging, labeling and label history in wine products with a focus on a case study of Hatten Wines in Bali. Packaging is explained as a wrapper that protects the product with a direct link to creative design and product information to facilitate marketing. Labels on wine have an important role as a means of conveying information, advertising and branding the product. The research method used is a descriptive qualitative approach to explore an in-depth understanding of the wine label phenomenon based on observation and literature analysis. The case study on Hatten Wines in Bali shows a change in their branding and labeling from traditional to minimalist and modern. The new label reflects Bali's distinctiveness and emphasizes the use of natural ingredients. Hatten Wines also uses QR Code technology to provide additional information to customers. Knowledge of the history of wine labels has a significant impact on the selection, purchase and promotion of wine products. Consumers who understand wine labels can make smart and knowledgeable choices about the products they purchase, while producers can design attractive and informative labels to increase consumer appeal. Thus, understanding the history of wine labels provides an appreciation of the rich history and culture behind each bottle of wine.